2016
DOI: 10.1002/chem.201603954
|View full text |Cite
|
Sign up to set email alerts
|

The Chemistry of a Non‐Interacting Vicinal Frustrated Phosphane/Borane Lewis Pair

Abstract: The dimesitylphosphinocyclopentene/HB(C F ) -derived vicinal trans-1,2-P/B frustrated Lewis pair (FLP) 4 shows no direct phosphane-borane interaction. Toward some reagents it behaves similar to an intermolecular FLP; it cleaves dihydrogen, deprotonates terminal alkynes, and adds to organic carbonyl compounds including CO . It shows typical intramolecular FLP reaction modes (cooperative 1,1-additions) to mesityl azide, to carbon monoxide, and to NO. The latter reaction yields a persistent P/B FLPNO nitroxide ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 166 publications
0
42
0
1
Order By: Relevance
“…These NMR shifts are in good agreement with data previously publishedf or zwitterionic phosphonium/alkynylborate compounds formed via the reactions of FLPs with phenylacetylene. [14] The 31 Pa nd 1 HNMR spectra of 2a in CD 2 Cl 2 ,h owever,a lso feature signals due to the FLP 1a and free phenylacetylene, which we hypothesized might be due to the presence of an equilibrium between PhCCH and its CÀHa ctivated form at room temperature. [14] The 31 Pa nd 1 HNMR spectra of 2a in CD 2 Cl 2 ,h owever,a lso feature signals due to the FLP 1a and free phenylacetylene, which we hypothesized might be due to the presence of an equilibrium between PhCCH and its CÀHa ctivated form at room temperature.…”
Section: Flp Reactivity Towards Alkynesmentioning
confidence: 84%
See 1 more Smart Citation
“…These NMR shifts are in good agreement with data previously publishedf or zwitterionic phosphonium/alkynylborate compounds formed via the reactions of FLPs with phenylacetylene. [14] The 31 Pa nd 1 HNMR spectra of 2a in CD 2 Cl 2 ,h owever,a lso feature signals due to the FLP 1a and free phenylacetylene, which we hypothesized might be due to the presence of an equilibrium between PhCCH and its CÀHa ctivated form at room temperature. [14] The 31 Pa nd 1 HNMR spectra of 2a in CD 2 Cl 2 ,h owever,a lso feature signals due to the FLP 1a and free phenylacetylene, which we hypothesized might be due to the presence of an equilibrium between PhCCH and its CÀHa ctivated form at room temperature.…”
Section: Flp Reactivity Towards Alkynesmentioning
confidence: 84%
“…For example, Erker et al report 11 Ba nd 31 PNMR shifts of d B = À17.6 and d P = 1.6 ppm ( 1 J PÀH = 490 Hz) for the product of CÀHc leavage by an anthracene-based intramolecular FLP, [13] and d B = À16.5 and d P = 0.0 ppm ( 1 J PÀH = 470 Hz) for ac yclopentanederived system. [14] The 31 Pa nd 1 HNMR spectra of 2a in CD 2 Cl 2 ,h owever,a lso feature signals due to the FLP 1a and free phenylacetylene, which we hypothesized might be due to the presence of an equilibrium between PhCCH and its CÀHa ctivated form at room temperature. Investigationb yv ariable temperature NMR spectroscopy revealed that the relative proportionso f1a/2a vary as af unction of temperature (K = 5.4 mm at 308 Kf or the loss of PhCCH;0 .61 mm at 198 K), and aV an't Hoff analysis (see Supporting Information) yields thermodynamic data (DH q =+34 kJ mol À1 ; DS q =+68 Jmol À1 K À1 )f or the loss of PhCCH from 2a.T hese data can be put into context by the corresponding values of + 38 kJ mol À1 and + 102 Jm ol À1 K À1 for the loss of H 2 from the phosphonium borate derived from the related FLP 1b.…”
Section: Introductionmentioning
confidence: 84%
“…In series II , FLPs in the close form are thermodynamically more stable, leading to relatively higher activation barriers (17.3–29.6 kcal mol −1 ) because breaking P…N bonding interaction is required for CO 2 activation. Similarly, Erker et al . reported that the development of open, non‐interacting and intramolecular P/B FLPs is significant towards small molecule activations including CO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…
Die japanische chemische Gesellschaft (CSJ) ehrte kürzlich bei ihrem Jahrestreffen eine Reihe herausragender Wissenschaftler, darunter Graham Fleming (University of California, Berkeley) und Gerhard Erker (Universität Münster) mit Ehrenmitgliedschaften für ausländische Forscher. Von Erker erschien in der Angewandten Chemie eine Arbeit über die metallfreie Allen‐Cyclotrimerisierung und in Chemistry—A European Journal eine über ein nicht wechselwirkendes benachbartes frustriertes Phosphan‐Bor‐Lewis‐Paar . Erker studierte an der Universität zu Köln und der Ruhr‐Universität Bochum.…”
Section: Ausgezeichnet …unclassified